Disease Profile and Outcome of Patients Admitted to A Pediatric Intensive Care Unit - Barua, Sanat Kumar; Deb, Kiriti Prashad; Dutta, Arup; Mahmud, Nasir Uddin; Chowdhury, Pranab Kumar; Barua, Sharmila (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Pediatric Intensive Care Unit (PICU) has very important role in the management of critically ill children who require advanced airway, respiratory, and hemodynamic supports with the aim of achieving a better outcome. To describe the clinical spectrum and outcome patterns of diseases managed at PICU in Chittagong Medical College Hospital (CMCH) in order to provide data, which will assist in improving the management of diseases and the rational allocation of health resources. Materials and methods: It was a retrospective crosssectional study in which records of admissions of children from 29 days to 12 years of age were obtained from the PICU records. Results: A total of 851 patients were analyzed during the period of October 2015 to December 2016, of which 533 (62.6%) were males and 318 (37.3%) were females. The mean duration of hospital stay was 5.2 ±2.1 days (Range 0- 20 days). Among admission cases, Central Nervous System (CNS) was the most common system affected in our study 356 (41%) followed by respiratory system 263(31%) sepsis 89(10.45%) and cardiovascular diseases 55(%). We observed overall mortality rate 46.1%and Leave Against Medical Advice (LAMA) 4.11%. Highest mortality occurred in age group of 29 days to 1 year. Children with encephalitis and sepsis had higher mortality 25% and 21% respectively. Conclusion: The leading cause of admission was CNS infection followed by respiratory diseases and sepsis. The overall mortality rate in our PICU was high. A wellequipped intensive care unit with modern and innovative facilities along with the availability of fulltime trained pediatric intensivists made a significant impact on the outcome of critically ill children in our PICU. JCMCTA 2018 ; 29 (1) : 11-16